ISOLATION AND IDENTIFICATION OF PIGMENT PRODUCING BACTERIA FROM SOIL - Vaishnavi Pankar,; Aarti Karpe,; Amruta Pawar,; Vaishali Kalasare,; Jadhav M, Zine A.S, (The Bioscan, 2024)
In present study the pigment producing microorganisms were isolated from different regions of Aurangabad district. Upon preliminary investigation, viz. colony characterization and grams staining, the suspected colony was observed to have a entire margin with a slightly raised elevation and gram negative, asporogenous. Biochemical analyses of the organism was done . The identity of the isolate was established via 16S rRNA, which strongly suggested it was Pseudomonas aeroginosa. The pigment produced by the isolate was applied for dying bioplastic. The use of synthetic dyes in these industry cause problems in environment such as toxicities. The synthetic dyes are not environment friendly. The natural colours are more advantage than synthetic colours, they have antibacterial, antifungal, anti-oxidant, anticancer activities etc.